A New Way of Data Interpretation for Cognition Tests in Rats Used to Characterise Six Choline Esterase Inhibitors with Heterocyclic Nitrogen Bridgehead Structure - Fleck, Christian; Appenroth, Dorothea; Decker, Michael; Lehmann, Jochen (Arzneimittelforschung, 2008)
Six new tri- and tetracyclic nitrogen bridgehead compounds known to be moderate to potent inhibitors of acetylcholinesterase (AChE) and butyrylcholin-esterase (BChE)in vitrowere testedin vivoas experimental therapeutics for treatment of Alzheimer’s disease. Cognitive impairment in rats was reversibly induced by scopolamine (CAS 51-34-3). The effect of the new substances was evaluated in an eight-arm radial maze and run times (1), errors (2), correct choices (3), correct choices per second (4), speed (5), and running distance (6) were recorded. For optimisation of data analysis a new strategy was used: A score was created on the basis of the 6 parameters described with score 1 for controls and score 4 for scopolamine rats. Scores above 4 indicate an impairment of cognition function compared to scopolamine. After equimo-lar dosage compared to the reference drug rivastigmine (CAS 123441-03-2), two of the new substances slightly improved cognition in rats, but only to a significantly lower degree compared to the irreversible inhibitor rivastigmine. Surprisingly, the other four compounds did not improve or even worsened the scopolamine effect on working memory.
Keywords: Acetylcholine; Acetylcholinesterase; Butyrylcholinesterase; Choline esterase inhibitors, data analysis, effect on memory; heterocyclic nitrogen bridgehead structure, radial maze, rat; Cognitive impairment, rat, scopolamine induced